Hemispheric dominance for visuospatial attention does not predict the direction of pseudoneglect. (November 2020) - Gerrits, Robin; Verhelst, Helena; Vingerhoets, Guy
Abstract: Pseudoneglect refers to a tendency of neurologically healthy individuals to produce leftward perceptual biases during spatial tasks, which is traditionally measured using line bisection tasks. This behavioral asymmetry is often explained as a consequence of right hemispheric dominance for visuospatial attention. The present study directly tested this notion by comparing line bisection performance between left-handers with either right hemispheric dominance (RVSD, N = 40) or "atypical" left hemispheric dominance (LVSD, N = 23) for visuospatial attention as determined by fMRI. Although we expected a reversal of pseudoneglect in participants with LVSD, our results show that they equally often err to the left of the true center compared to RVSD controls (74% of LVSD participants and 80% of RVSD participants). However, the magnitude of misbisections was found to be slightly, but significantly, smaller in the LVSD subgroup.We conclude that hemispheric asymmetry for visuospatial attention is not the main determinant of pseudoneglect as is commonly thought, but rather only constitutes one of the multiple factors which (subtly) contributes to its direction and magnitude. Highlights: Hemispheric dominance for visuospatial attention (VSD) was determined with fMRI. Pseudoneglect was measured using a pen-and-paper line bisection task. Leftward pseudoneglect was found in both left and right hemisphere VSD subgroups. Misbisection errors were smaller in magnitude in left hemisphere VSD participants. VSD does not seem to be the main determinant of pseudoneglect as is often thought.